Knowledge and Misconceptions about HIV Counseling and Testing (HCT) among the Post-Conflict Youths of Gulu, Northern Uganda. A Prospective Study Design - Kitara, David Lagoro; Amone, Charles; Okello, Christopher (Pan African Medical Journal, 2012)
Uganda has been reported as the most successful country in Africa in reducing the prevalence of HIV/AIDS from 18% to 6.4% over the last two decades. There is evidence to suggest that despite a significant decline between 1992 and 2002, HIV prevalence has stagnated over the last 5-9 years at between 6.1 and 6.5% and it is rising in some parts of the country such as Gulu. This rise are thought to be due to the high levels of stigma and superstition preventing HIV counseling and testing (HCT). WHO reports in 2009 showed that only 20% of Uganda’s populations knew their HIV sero-status. This study was designed to find out the knowledge, misconceptions, attitude and practices of youths of Gulu about HCT. Methods: A cross-sectional study was conducted in Gulu, Pece among the youths 15 to 35 years. An in-depth interview using a questionnaire was administered to youths of Commercial Road Sub-ward. Informed consent and ethical approval was obtained and 86 respondents were interviewed. Results: Ninety three percent of respondents had knowledge about HCT and 97.7% were able to mention two or more of its benefits. Most (88.4%) agreed on public disclosure of their HIV status and 84.9% would encourage others to undertake it. Only 36.1% of respondents had undertaken HCT while the rest had not undertaken it due to fear of stigmatization. There is adequate knowledge, good attitude but poor practice and misconceptions to HCT. The young adults in Gulu should be supported in a special program to enable them undertake HCT and access other services for HIV/AIDS prevention.
Keywords: Knowledge, youths, HIV counseling and testing (HCT), post-conflict, Uganda